PEMBERIAN KOMPRES AIR HANGAT TERHADAP PENURUNAN SUHU TUBUH PADA ASUHAN KEPERAWATAN DENGAN DEMAM TYPOID DI RUMAH SAKIT BHAYANGKARA M HASAN PALEMBANG TAHUN 2022 - Tuti Elyta; Sari Octarina Piko; Jurni Oktavia (Pusat Riset dan Inovasi Nasional, 2023)
Typhoid fever is an acute infectious disease that usually affects the digestive tract with symptoms of fever that last more than one week. Non-pharmacological techniques in reducing fever body temperature are warm water compresses. The purpose of this study is to find out a description of the provision of warm water compresses to decrease body temperature in typhoid fever.The design of this research is descriptive analytic with Case Study method. The management of typhoid fever is giving warm water compresses to decrease body temperature which is carried out at Bhayangkara M Hasan Hospital Palembang from June 14, 2022 to June 16, 2022. The subjects of this study were 2 patients with Typhoid Fever. The plan given is the provision of warm water compresses to decrease body temperature in typhoid fever. The research instrument used is the format of nursing care and medical records. While the instrument for measuring body temperature uses a thermometer and the instrument for giving warm water compresses uses nierbeken, warm water (43-46℃), washcloth and swab. After giving warm water compresses for 3 days, both patients experienced a decrease in body temperature. The body temperature of Mrs.